Mature Teratoma Intrapulmonary in Adolescent - SIREGAR, OLGA RASIYANTI; LESTARI, WAHYUNINGSIH; ROSDIANA, NELLY (Indonesian Journal of Cancer, 2014)
Mature teratoma is the most common primary germ cell tumor in the mediastinum, but very rare in the lung. A very rare case of mature giant intrapulmonary teratoma in a 14 year old female is reported. She had chronic cough, recurrent fever, chest pain, weight loss and history of breathless for six months. A chest x-ray showed a large mass with atelectasis of the left lung and thoracic CT scan revealed a giant neoplasm of the left lung, sized about 13x19 cm with calcification. The patient underwent left thoracotomy posterolateral, the tumor was totally resected with pneumonectomy. The histopatological examination revealed a mature teratoma. Intrapulmonary teratoma is very rare tumors with nonspecific signs and symptoms. Total removal tumor is the treatment of choice for this type of teratoma.